HYAL-2–WWOX–SMAD4 Signaling in Cell Death and Anticancer Response - Hsu, Li-Jin; Chiang, Ming-Fu; Sze, Chun-I; Su, Wan-Pei; Yap, Ye Vone; Lee, I-Ting; Kuo, Hsiang-Ling; Chang, Nan-Shan (Frontiers in Cell and Developmental Biology, 2016)
Hyaluronidase HYAL-2 is a membrane-anchored protein and also localizes, in part, in the lysosome. Recent study from animal models revealed that both HYAL-1 and HYAL-2 are essential for the metabolism of hyaluronan (HA). Hyal-2 deficiency is associated with chronic thrombotic microangiopathy with hemolytic anemia in mice due to over accumulation of high molecular size HA. HYAL-2 is essential for platelet generation. Membrane HYAL-2 degrades HA bound by co-receptor CD44. Also, in a non-canonical signal pathway, HYAL-2 serves as a receptor for transforming growth factor beta (TGF-β) to signal with downstream tumor suppressors WWOX and SMAD4 to control gene transcription. When SMAD4 responsive element is overly driven by the HYAL-2–WWOX–SMAD4 signaling complex, cell death occurs. When rats are subjected to traumatic brain injury, over accumulation of a HYAL-2–WWOX complex occurs in the nucleus to cause neuronal death. HA induces the signaling of HYAL-2–WWOX–SMAD4 and relocation of the signaling complex to the nucleus. If the signaling complex is overexpressed, bubbling cell death occurs in WWOX-expressing cells. In addition, a small synthetic peptide Zfra (zinc finger-like protein that regulates apoptosis) binds membrane HYAL-2 of non-T/non-B spleen HYAL-2+ CD3- CD19- Z lymphocytes and activates the cells to generate memory anticancer response against many types of cancer cells in vivo. Whether the HYAL-2–WWOX–SMAD4 signaling complex is involved is discussed. In this review and opinion article, we have updated the current knowledge of HA, HYAL-2 and WWOX, HYAL-2–WWOX–SMAD4 signaling, bubbling cell death, and Z cell activation for memory anticancer response.